Medication Adherence and Growth in Children with CKD - Akchurin, Oleh M. (American Society of Nephrology, 2014)
BACKGROUND AND OBJECTIVES: Poor growth is a consequence of CKD, but can often be partially or fully prevented or corrected with the use of a number of medications. The extent of nonadherence with medications used to treat or mitigate growth failure in CKD has not been examined prospectively in children with CKD. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: The prevalence of both prescription of and nonadherence to recombinant human growth hormone (rhGH), phosphate binders, alkali, active vitamin D, nutritional vitamin D, iron, and erythrocyte-stimulating agents was summarized over the first seven visits of the Chronic Kidney Disease in Children cohort study. The association between self-reported nonadherence to each medication group and the mean annual change in age- and sex-specific height z score was quantified using seven separate linear regression models with generalized estimating equations. RESULTS: Of 834 participants, 597 reported use of at least one of these medication groups and had adherence data available. Nonadherence ranged from 4% over all visits for erythrocyte-stimulating agents to 22% over all visits for nutritional vitamin D. Of the study participants, 451 contributed data to at least one of the analyses of adherence and changes in height z score. Children nonadherent to rhGH had no change in height z score, whereas those adherent to rhGH had a significant improvement of 0.16 SDs (95% confidence interval, 0.05 to 0.27); the effect size was slightly larger and remained significant after adjustment. Among participants with height≤3rd percentile and after adjustment, adherence to rhGH was associated with a 0.33 SD (95% confidence interval, 0.10 to 0.56) greater change in height z score. Nonadherence with other medication groups was not significantly associated with a change in height z score. CONCLUSIONS: Self-reported nonadherence to rhGH was associated with poorer growth velocity in children with CKD, suggesting an opportunity for intervention and improved patient outcome.